Biodegradation of polyethylene in digestive gland homogenates of marine invertebrates - Istomina, Aleksandra; Chelomin, Victor; Mazur, Andrey; Zhukovskaya, Avianna; Karpenko, Alexander; Mazur, Marina (PeerJ, 2024)
Вiotic factors may be the driving force of plastic fragmentation along with abiotic factors. Since understanding the processes of biodegradation and biological depolymerization of plastic is important, a new methodological approach was proposed in this study to investigate the role of marine invertebrate digestive enzymes in plastic biodegradation. The aim of this study is to evaluate the possibility of enzymatic biodegradation of polyethylene fragments in the digestive gland homogenate of marine invertebrates differing in their feeding type (Strongylocentrotus nudus, Patiria pectinifera, Mizuhopecten yessoensis). Significant changes are found in the functional groups of the polymer after 3 days of incubation in the digestive gland homogenates of the studied marine invertebrates. A significant increase in the calculated CI (carbonyl index) and COI (сarbon-oxygen index) indices compared to the control sample was observed. The results suggest that digestive enzymes of studied organisms may play an important role in the biogeochemical cycling of plastic.
Keywords: Biodegradation of plastic; Fourier transform infrared spectroscopy